Does Poor Dental Health Have a Role in the Emergence of Variant Creutzfeldt Jakob Disease in the United Kingdom? - Robert Burnie; Roland L Salmon; Daniel R Thomas; Nigel Monaghan (Dental Hypotheses, 2011)
Introduction: Variant creutzfeldt jakob disease (vCJD) is the hu-man neurological disease known to be caused by the same proteinaceous infectious agent (“prion”) that causes Bovine Spongiform Encephalopathy or "Mad Cow Disease". Two un-usual and unexplained characteristics of the vCJD epidemic are its geographical distribution within the UK (about twice as frequent in Scotland and Northern England) and its median age of onset of 26 years that has remained unchanged over the fifteen years of the epidemic.The hypothesis: Infection via the dental route as a consequence of poor dental health, most probably the presence of untreated decay may account for the geographical distribution of vCJD in the UK and offer an explanation for the constant median age of onset of the dis-ease by representing a fixed stage in development.Evaluation of the hypothesis: Analysis of existing data indicates that vCJD incidence by region and an index of dental health by region are positively correlated (r=0.737, p= 0.015). The hypothesis that infection via the dental route may explain the constant median age of onset and geographical distribution of vCJD could be investigated further with a case control study based on individual dental records and by further animal experiments to confirm the biological plausibility of this route.